2020
DOI: 10.1136/bmjopen-2019-035504
|View full text |Cite
|
Sign up to set email alerts
|

Role of endoscopic ultrasonography in the diagnostic work-up of idiopathic acute pancreatitis (PICUS): study protocol for a nationwide prospective cohort study

Abstract: IntroductionIdiopathic acute pancreatitis (IAP) remains a dilemma for physicians as it is uncertain whether patients with IAP may actually have an occult aetiology. It is unclear to what extent additional diagnostic modalities such as endoscopic ultrasonography (EUS) are warranted after a first episode of IAP in order to uncover this aetiology. Failure to timely determine treatable aetiologies delays appropriate treatment and might subsequently cause recurrence of acute pancreatitis. Therefore, the aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…This may raise the question whether follow‐up imaging would allow for an earlier diagnosis in idiopathic pancreatitis patients. As follow‐up imaging has previously been proposed for these patients to further investigate etiology and identify the need of a cholecystectomy, screening for pancreatic cancer may be another indication 28,29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may raise the question whether follow‐up imaging would allow for an earlier diagnosis in idiopathic pancreatitis patients. As follow‐up imaging has previously been proposed for these patients to further investigate etiology and identify the need of a cholecystectomy, screening for pancreatic cancer may be another indication 28,29 …”
Section: Discussionmentioning
confidence: 99%
“…As follow-up imaging has previously been proposed for these patients to further investigate etiology and identify the need of a cholecystectomy, screening for pancreatic cancer may be another indication. 28,29 Several important findings emerged from our data when examining risk factors for disease transition. Consistent with other studies, the highest cumulative incidence of RAP and CP was observed among alcoholic pancreatitis patients.…”
mentioning
confidence: 80%
“…Not infrequently, the underlying cause of an acute pancreatitis episode remains obscure even after standard clinical, biochemical, and radiological (US and CT) evaluation, creating a subgroup of acute pancreatitis referred to as acute idiopathic pancreatitis (AIP) [ 25 ]. Previous studies have shown that an EUS examination might be beneficial in exploring the underlying cause of a presumed AIP [ 26 ]. During an episode of AIP, the yield of EUS in exploring the pancreatic parenchyma and ducts is very limited given the presence of edema of the duodenal wall, pancreatic inflammation, necrosis, or peri-pancreatic fluid collection, as these can deeply hinder the visualization of the pancreas, and occasionally the gallbladder or bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…All patients provided written informed consent. The study protocol was registered at the Netherlands Trial Registry (NL7066) and published 10 . This study was reported in accordance with the STROBE statement for cohort studies 11 and the STARD statement 12 ( Table S1 ).…”
Section: Methodsmentioning
confidence: 99%